Original paperPermanent prostate brachytherapy extracapsular radiation dose distributions: analysis of a multi-institutional database - Merrick, Gregory S.; Butler, Wayne M.; Grimm, Peter; Morris, Mallory; Lief, Jonathan H.; Bennett, Abbey; Fiano, Ryan (Journal of Contemporary Brachytherapy, 2013)
Purpose : Periprostatic brachytherapy doses impact biochemical control. In this study, we evaluate extracapsular volumetric dosimetry following permanent prostate brachytherapy in patients entered in a multi-institutional community database. Material and methods : In the database, 4547 patients underwent brachytherapy (3094 – 125 I, 1437 – 103 Pd and 16 – 131 Cs). Using the originally determined prostate volume, a 5 mm, 3-dimensional peri-prostatic anulus was constructed around the prostate (except for a 2 mm posterior margin), and evaluated in its entirety and in 90° segments. Prostate dosimetric parameters consisted of a V 100 and D 90 while the annular dosimetry was reported as a V 100 . Results : The intraprostatic V 100 and D 90 for 103 Pd, and 125 I were statistically comparable when stratified by isotope and/or monotherapy vs. boost. The overall mean V 100 for the periprostatic annulus was 62.8%. The mean V 100 at the base (51.6%) was substantially less than the apex (73.5%) and midgland (65.9%). In addition, for all patients, the anterior V 100 (45.7%) was less than the lateral (68.8%) and the posterior (75.0%). The geometric V 100 annular differences were consistent when evaluated by isotope. Overall, the V 100 was higher in the 125 I cohort. Conclusions : The optimal extracapsular brachytherapy dose and radial extent remains unknown, but will prove increasingly important with reductions and/or elimination of supplemental external beam radiation therapy. The large multi-institutional community database demonstrates periprostatic annular doses that are not as robust as those in selected high volume brachytherapy centers, and may be inadequate for optimal biochemical control following monotherapeutic brachytherapy, especially in higher risk patients.